Exploration of Place Brand Attributes: A Study of Bangalore City - Vandewalle, Ian; Phadke, Suniti (Indian Journal of Marketing, 2008)
The study is based on quantitative exploration of Place Brand attributes using Bangalore as a case study. This paper determines the city attributes of Bangalore along with its three competing cities for the position of ’The Top Place Brand in South India.’ Focus Group discussions were first carried out to identify six key place brand attributes. These comprised three Functional Attributes (shopping and attractions; service and amenities; and physical re-development) and three Representational Attributes (civic status and prestige; character, heritage and culture; and a pleasant city to live in). The Quantitative Method expounded by Romaniuk and Sharp (2000) was used to rank perceptions of both Functional and Representational City Attributes. A comparison of expected against observed results indicate which city attributes are viewed as positive and which are viewed as negative. The study of the place brand attributes may provide strategic direction to the city authorities and brand managers to plan ahead.